Protocolos en rehabilitación estética de carillas de cerámica - Liliana Stefany, Cazco Paredes (2022)
ABSTRACT Ceramic veneers are very thin porcelain shells that are adhered to the tooth surface and are a minimally invasive treatment used to restore esthetics, harmony, and occlusion. This review of the literature analyzes the protocols in esthetic rehabilitation of ceramic veneers, with the aim of describing them for dental preparation, taking the definitive impression, provisionalization and cementation. It was carried out by means of a bibliographic study of scientific articles published from 2016 to 2021, extracted from databases such as: PubMed, Elsevier, Science Direct, Worldwide science and Google Scholar, through criteria of inclusion, exclusion, and to measure the quality of the studies the PICOs method was applied, the average citation count (ACC), and the impact factor index in which the article was published according to the Scimago Journal Ranking (SJR), obtaining a total of 70 articles for the systematic review. It was concluded that tooth preparation should be limited to the enamel since the clinical longevity of the veneers depends on it, a mock-up driven preparation protocol was described, a provisionalization protocol using bisacrylic resin was described and the procedures to be performed on the ceramic and tooth structure for veneer cementation were specified step by step, as well as a mention of the latest advances and modifications that exist today thanks to technological advances. Key words: Protocols, ceramic veneers, tooth preparation, dental impression, provisionalization and cementation.